Medication beliefs and use of medication lists - is there a connection?: results from a before-and-after study in Germany - Straßner, Cornelia; Mahler, Cornelia; Strauß, Beate; Wehrmann, Ulrich; Krug, Katja; Szecsenyi, Joachim; Haefeli, Walter E.; Seidling, Hanna (BMC geriatrics, 2020)
Despite increasing digitalisation the paper-based medication list remains one of the most important instruments for the documentation and exchange of medication-related information. However, even elderly patients with polypharmacy who are at high risk for medication errors and adverse drug events, frequently do not receive or use a complete and comprehensible medication list. Increasing the use of medication lists would be a great contribution to medication safety and facilitate the work of health care providers.
Gesehen am 20.04.2020